The Motions Beneath : Indigenous Migrants on the Urban Frontier of New Spain - Corbeil, Laurent (Book collections on Project MUSE., 2018)
"An urban history of the valley of San Luis Potosí from 1590 to 1630, examining the relationships among the large number of initially distinct indigenous populations; Tlaxcalan, Tarrascan, and Otomí settlers; and the region's existing ethnic communities"--Provided by publisher.